Prof. Dr. Fatou Sow "Relating Women in African Studies: A Critical View" (Conference Modalities 2021, 2021)
For the opening of its second international conference the Africa Multiple Cluster of Excellence invited the distinguished Senegalese sociologist, Prof. Dr. Fatou Sow, to speak about "Relating Women in African Studies: A Critical View". Fatou Sow was introduced by Prof. Dr. Akosua Adomako Ampofo. The event was chaired by Prof. Dr. Ute Fendler, the Cluster's Vice Dean of Internationalisation and Public Engagement. After Sow’s keynote, the Dean of the Bayreuth International Graduate School of African Studies (BIGSAS), Prof. Dr. Martina Drescher, solemnly announced that the distinguished Senegalese scholar, a veritable pioneer of African feminist studies, has been selected as the recipient of the BIGSAS honorary doctorate, making her the second person to be awarded this title to date To find out more about Prof. Sow receiving the BIGSAS honorary award: https://www.africamultiple.uni-bayreuth.de/en/news/2021/2021-07-14_Fatou_Sow/index.html